Herding Behavior and ESG Performance During a Crisis : Evidence from the EURO STOXX 50 in the context of COVID-19 - Peltola, Elina (My University, 2025)
This thesis investigates herd behavior in Europe during the COVID-19 pandemic and whether ESG scores amplify this behavior. The analysis utilizes data from the EURO STOXX 50 companies for the period from 2020 to 2022. This thesis employs the cross-sectional absolute deviation (CSAD) to measure the degree of herding based on Chang et al.'s (2000) model. The model further incorporates ESG scores and interaction terms capturing the effect of the COVID-19 pandemic, following the approach of Gavrilakis and Floros (2023). The results suggest that a higher ESG score is not associated with stronger herding behavior. The results imply that ESG transparency may reduce informational asymmetry, encouraging more independent investor behavior. Similarly, the hypothesis of herding behavior intensifying during the COVID-19 outbreak is not supported. Extreme market conditions do not increase the dispersion of the returns in this dataset. This challenges previous literature that suggests stronger herding during a crisis. Overall, the results of this thesis suggest that neither ESG performance or the COVID-19 pandemic significantly increased herding behavior in EURO STOXX 50 firms. It proposes that these large-cap and liquid companies may mitigate herd tendencies. The findings highlight the importance of context when analyzing herding and suggest that future research should explore the role of ESG in less transparent or smaller-cap markets.
Keywords: COVID-19; herding; regression analysis; responsible investing; pandemics; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Laskentatoimen ja tilintarkastuksen maisteriohjelma|en=Master's Programme in Accounting and Auditing|